Analisis Pendidikan Bermutu Melalui Tugas dan Kompetensi Supervisor - Zeinal Abidin; Siti Maizah (Medan Resource Center, 2023)
This abstract aims to discuss the importance of supervision in achieving quality education and fostering competent teachers. Education plays a vital role in developing a superior generation with character, aligned with the national philosophy of Pancasila, and contributing to society, the nation, and the state. In the current era of globalization, where competitiveness is crucial, quality education becomes essential. Supervision activities conducted by supervisors significantly contribute to the progress of education. Through effective supervision and guidance, teachers can enhance their skills and ultimately improve students' learning outcomes. Both principals and supervisors should possess the necessary understanding of their roles and responsibilities in order to produce qualified teachers. Several competencies are required to fulfill these tasks successfully. This study emphasizes the significance of supervision in shaping the educational landscape and the role of competent supervisors in fostering quality education.